The Role of Jaish Al-Adl Group in the Escalation of Conflict on the Iran-Pakistan Border - R, Febiana; Burhanuddin, Agussalim (Global Mind, 2023)
Jaish Al-Adl is an ethnic Baloch Sunni Muslim militant group that has played a significant role in the escalation of conflict on the Iran-Pakistan border. Jaish Al-Adl was founded in 2012 and is largely composed of members of the Sunni Jundullah militia that was weakened after Iran captured the majority of its members. Jaish Al-Adl wants to liberate Sistan province in eastern Iran and Balochistan province in southwestern Pakistan. This paper will elaborate on the relationship between Iran and Pakistan, especially in the context of borders by using a qualitative approach that utilizes various secondary data that has a correlation with the role of Jaish Al-Adl in worsening relations between Iran and Pakistan. By using descriptive type, this paper will explain the situation and empirical facts accompanied by relevant arguments and show Jaish Al-Adl's controversial activities, so that Jaish Al-Adl is labeled as a militant group that further worsens relations between Iran and Pakistan.